Methodology for measuring postharvest quantity and quality losses - CGIAR Research Program on Policies, Institutions, and Markets (2020)
FAO and PIM used the methodology in 11 countries. FAO's 2019 "State of Food and Agriculture" report on food losses used PIM outputs. The methodology was implemented in Ghana through an SNV (Netherlands Development Organisation) project. Results of the methodology are used to inform the UN 2020 Food Systems Summit.